The Collective Risk of Inequality: a Social Dilemma calling for a Solution? - Philipp Poppitz (Hamburg University, Department Economics and Politics, 2011)
In the aftermath of the financial crisis, attention concerning inequality as a risk factor has risen. Nevertheless studies, focusing on the implications of inequality as a collective risk, remain seldom. Therefore the following paper will discuss why inequality is indeed a collective risk, leading to a social dilemma as known from game theory. The first section examines the collective risks that emerge of disproportionate income distribution and social immobility - as two dimensions of inequality. The second section investigates how these inequalities and their resulting collective risks can remain persistent. Climate change as a risk factor, shares several features with the dynamics of inequality. This will be demonstrated, by applying the results of an experimental study on climate change on the afore mentioned discussion and analysing the implications of additional aspects as unequal initial endowments and strong reciprocity. The paper concludes that the contribution of individuals to lower inequality is highly dependent on the expected probability of risk. If the risk probability is not close to one, contributions are low and cannot reduce inequality substantially while risks remain persistent.
Keywords: C71; D81; H41; Z13; 330; Inequality; Social Mobility; Collective Risk; Snow Drift Game